Nursing guidelines for people with intestinal ostomy in extra-hospital scenario: scoping review. - Freitas, Luana Souza; Mesquita, Simone Karine da Costa; Nascimento, Rafael Moreira do; Fernandes, Mariana Freire; de Oliveira e. Araújo, Rhayssa; Costa, Isabelle Katherinne Fernandes (UERJ Nursing Journal / Revista Enfermagem UERJ, 2023)
Objective: to map in the literature the nursing guidelines for people with intestinal ostomies in primary health care and referral centers. Method: scoping review developed in April and May 2022, in national and international bases and gray literature sources. The descriptors were used: Ostomy; Colostomy; Ileostomy; Health Education; Primary Attention; Health Services and their English translations. Followed the steps recommended by the Joana Briggs Institute and registered on the Open Science Framework platform. Results: were identified 2242 studies, 17 of which were selected for sample composition. The guidelines focused predominantly on self-care with ostomy and peristomal skin, choice of collector and adjuvant equipment and aspects of acceptance and adaptation. Conclusion: the main nursing guidelines for people with ostomy were identified in the literature. The study contributes to nursing practice in view of the reasoning of the needs and qualified care to be provided to the person with an ostomy in the integrality of care.